222k views
4 votes
Hey this text is just for min word requirement the problem is in the picture

Hey this text is just for min word requirement the problem is in the picture-example-1
User Kevork
by
4.4k points

2 Answers

6 votes

Answer:

(-2, 0)

Explanation:

User Simon Kjellberg
by
5.4k points
5 votes

Because both equations are to find Y, set them equal to each other to solve:

3x+6 = x+2

Subtract x from both sides:

2x + 6 = 2

Subtract 6 from both sides:

2x = -4

Divide both sides by 2:

x = -4 /2

x = -2

Now you have a value for x, replace X with -2 in one of the equations and solve for y:

y = 3x +6 = 3(-2) +6 = -6 +6 = 0

X = -2 and Y = 0

(-2,0)

User Jay Fridge
by
4.4k points